Investigation of energy transport in DIII-D High-βP EAST-demonstration discharges with the TGLF turbulent and NEO neoclassical transport models. (11th January 2017) - Pan, C.; Staebler, G.M.; Lao, L.L.; Garofalo, A.M.; Gong, X.; Ren, Q.; McClenaghan, J.; Li, G.; Ding, S.; Qian, J.; Wan, B.; Xu, G. S.; et al.
Abstract: Energy transport analyses of the DIII-D high- β P EAST-demonstration discharges have been performed using the TGYRO transport package with the TGLF turbulent and NEO neoclassical transport models under the OMFIT integrated modeling framework. Ion energy transport is shown to be dominated by neoclassical transport and ion temperature profiles predicted by TGYRO agree closely with the experimental measured profiles for these high- β P discharges. Ion energy transport is largely insensitive to reductions in the E × B flow shear stabilization. The Shafranov shift is shown to play a role in the suppression of the ion turbulent energy transport below the neoclassical level. Electron turbulent energy transport is under-predicted by TGLF and a significant shortfall in the electron energy transport over the whole core plasma is found with TGLF predictions for these high- β P discharges. TGYRO can successfully predict the experimental ion and electron temperature profiles by artificially increasing the saturated turbulence level for ETG driven modes used in TGLF.